Exploring through the use of physiological and isotopic techniques the potential of a PGPR-based biofertilizer to improve nitrogen fertilization practices efficiency in strawberry cultivation - García-López, Jesús V.; Redondo-Gómez, Susana; Flores-Duarte, Noris J.; Zunzunegui, María; Rodríguez-Llorente, Ignacio D.; Pajuelo, Eloísa; Mateos-Naranjo, Enrique (Frontiers in Plant Science, 2023)
The use of microorganisms as a biofertilizer in strawberry has focused mainly on pathogen biocontrol, which has led to the underestimation of the potential of microorganisms for the improvement of nutritional efficiency in this crop. A study was established to investigate the impact of a plant growth-promoting rhizobacteria (PGPR) based biofertilizer integrated by self-compatible stress tolerant strains with multiple PGP properties, including atmospheric nitrogen fixation, on strawberry (Fragaria × ananassa cv. Rociera) tolerance to N deficiency in terms of growth and physiological performance. After 40 days of nitrogen fertilization shortage, inoculated plants were able to maintain root development and fertility structures (i.e. fruits and flowers) at a level similar to plants properly fertilized. In addition, inoculation lessened the negative impact of nitrogen deficiency on leaves’ dry weight and relative water content. This effect was mediated by a higher root/shoot ratio, which would have allowed them to explore larger volumes of soil for the acquisition of water. Moreover, inoculation was able to buffer up to 50% of the reduction in carbon assimilation capacity, due to its positive effect on the diffusion efficiency of CO2 and the biochemical capacity of photosynthesis, as well as on the activity of photosystem II light harvesting. Furthermore, the higher leaf C/N ratio and the maintained δ15N values close to control plants were related to positive bacterial effects at the level of the plant nutritional balance. Despite these positive effects, the application of the bacterial inoculum was unable to completely counteract the restriction of fertilization, being necessary to apply a certain amount of synthetic fertilizer for the strawberry nutrition. However, according to our results, the complementary effect of this PGPR-based biofertilizer could provide a higher efficiency in environmental and economic yields on this crop.